Strategies, Successes, and Gaps in Algebra Teaching: A Scoping Review - Hamidah, Ida; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Pramuditya, Surya Amami (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2025)
Algebra is a fundamental component of mathematics education that supports students’ success in higher-level mathematical learning. However, many students struggle to understand algebraic concepts due to their abstract nature and the limited use of effective instructional strategies. This scoping review aims to (1) identify how algebra teaching activities are represented in the literature, (2) explore the main instructional themes and approaches discussed, and (3) examine existing research gaps that require further study. A total of 143 studies published between 2015 and 2025 were retrieved from the Scopus database, and after a rigorous screening process, six studies met the inclusion criteria for full analysis. The review identified five dominant instructional themes: contextual problem-based learning, visual and concrete representations, technology-enhanced and game-based learning, collaborative discussions, and reflective reasoning. These approaches were found to enhance students’ engagement, conceptual understanding, and algebraic reasoning. Nevertheless, significant gaps remain in early algebra instruction, teacher professional development, and the integration of emerging technologies in classroom practice. The findings underscore the need for innovative, inclusive, and technology-integrated teaching strategies to strengthen students’ algebraic thinking and improve the quality of mathematics education.